Fear of Covid-19 And Work Engagement as Predictors of Psychological Distress in Medical Residents - Kristiana Haryanti; Maria Mexitalia; Widawati Hapsari; Maria Bramanwidyantari; Wistiani Wistiani; Julian Dewantiningrum; Yudo Murti Mupangati; Muyassaroh Muyassaroh; Anna Mailasari Kusuma Dewi (Universitas Ahmad Dahlan, 2022)
This study aimed to see whether the Fear of Covid-19 and work engagement affect depression, anxiety, and stress of resident doctors. Pandemic situation of Covid-19 is not over yet with viral mutations from Covid-19 Delta to Omicron variants. Residents doctors were obliged to help in treatment even though their main duty was focusing on their study. As the Covid-19 is a deadly situation and should be handled with many safety protocols, this situation can be anxious for both the patient and the medical staff (including the residents) who work daily in hospital. This study focused on 877 public hospital residents Fear of Covid-19, depression, anxiety and stress. Regression analysis and Structural Equation Modeling (SEM) were used as statistical tools. The results showed that both Fear of Covid-19 and work engagement affect depression, anxiety, and stress. This article also details the impact of each aspect measured in this study.